A methods engineering study for Antonina Industrial Corporation - Flores, Ma. Criselda M.; Sumalabe, Marian U.; Peñaflorida, Karen Kristin (Diliman, Quezon City College of Engineering, 2003)
This study is conducted to increase the productivity of Antonina Industrial Corporation, specifically in their packing area. The aim is to reduce the total time of packing one knock-down carton of coffee sachets, so as for the workers to finish their daily quota during the regular working hours. This will be made possible by eliminating non-value adding elements in the process, and decreasing any travel time and distance. Problems in the company are identified by different methods. Plant visits are conducted in order to view the production system of the company. Direct observations are made to the different processes involved. The machines, manpower, procedures and quality measures for each process are identified and analyzed, through which most of the problems are identified. Company standards are also reviewed, especially the quota set for the workers in the packing area. The operation in the packing area is divided into elements, and time study is conducted to measure each elemental time. The total time computed for the actual operation of packing to inner cartons (8.42 min/case) is then compared to the standard set by the company. After determining the problem involved in the production areas, the group established the relationships of the problems through a stream diagnosis chart. Several issues are identified as the root causes, and each problem is evaluated. The problem "slow packing pace" is then identified as the root cause of several areas in the production and warehouse facilities. This issue is then analyzed by using a cause and effect diagram. Through this method, the problem on the work layout is established as the root cause of slow packing pace. Three alternatives to the present work layout are gathered, and each alternative includes a proposal on a standard way of job assignment. Each alternative is then evaluated against the present layout. The second proposed layout is chosen since it gives the least distance traveled by the handler of knock down cartons, and gives an effective assignment of task to each worker. The new layout is tested, and another time is conducted to verify any improvement made in the process. A decrease in the total cycle time of 0.79 minutes per case is observed as compared to the present method, or a reduction of 53.4 minutes per working day. This is an improvement considering that the new layout results to a standard time nearer to that set by the company as opposed to the standard time of the old layout.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Antonina Industrial Coporation; Manufacturing industry; Systems analysis